Interações espaciais entre cidade média e pequenas cidades: um estudo de Araguaína-TO, Campos Lindos-TO, Carolina-MA e São Geraldo do Araguaia-PA - Dias, Reges Sodré da Luz Silva (2016)
This research investigates the roles played and the interactions established by smalltowns in the area of influence of Araguaína-TO, which is the second largest urban center of the Tocantins, offering a wide range of goods and services to the regional contexto. Among the 26 cities under its area of influence, Carolina, São Geraldo do Araguaia and Campos Lindos, highlight in various economic and population indicators, such as higher GDP, population and agricultural production. The research focuses on the understanding of these small towns, from the centrality and spatial interactions produced by the economic activities that they have with other centers and displacement of its residents. In terms of methodology, the study presentes a qualitative and quantitative approach. Quantitative procedures are focused on characterization of small towns directly influenced by Araguaína, according to the classification of the IBGE (2008), collecting secondary data from various agencies and institutions. With regard to qualitative procedures, through simple observation go through the streets of São Geraldo do Araguaia, Carolina and Campos Lindos, with diary, when possible making notes of all the shops and main services offered, as well as elements for the realization of thematic maps. We also semi-structured interviews with the use of two types of forms, the first, for the population of the urban area and the other with the owners and responsible for comercial establishments. Among the elements that redefine the urban network are the new information technologies, the expansion of consumption among low-income workers, and the advance of agribusiness and timid industrial desconcentration. In analytical terms, there are new approaches that proposes explanations to these elements. Among which stands out the articulation of geographic scales, in which the spatial interations become interescalares. In small cities under study, modernizations processes are very recente and realized with extreme contradiction, because of higher poverty rates. The new dynamics that redefines national urban network, are not indiferente in the region under study, kept their specificities and care should be taken when making analogies general processes, they have to show themselves capable of imposing new elements to think about the network cities. On the one hand, the medium-sized cities has its supported functions in interescalares and hierarchical spatial interactions, subordinating the small towns on the other, these cities at the same time are subject to average city, partially subvert this hierarchy, espacially through new technologies and strengthening agribusiness.